Exploring SMEs Marketing Performance Through Networking Capacity and Relational Capability - Nuryakin Nuryakin (APMBA (Asia Pacific Management and Business Application), 2020)
This research aims to analyse the effect of relational capability and networking capacity on SMEs marketing performance of Wooden Handicraft in one of the heritage area in Indonesia, in the area of Klaten, Bantul  and Sleman Regency of Yogyakarta.By occupied sampling technique of purposive sampling, several criteria used in the sampling were Wooden Handicraft Export SMEs that have been operating for three years or more. Total of 140 questionnaire utilized in this study resulting 129 respondents studied. The results showed that relational capability had a significant effect on SMEs marketing performance. Relational capability had a significant effect on networking capacity. Also, networking capacity had a significant effect on SMEs marketing performance.